Rancang Bangun Sistem Inventaris Sekolah Berbasis Website Dengan Metode Waterfall : (Studi Kasus Pada YP. Rahmat Islamiyah) - Arif Rahman; Muhammad Khaibar Putra Aditya; Satriandi (Pusat Riset dan Inovasi Nasional, 2026)
Inventory management at the Rahmat Islamiyah Educational Foundation is still conducted manually, leading to risks of data loss, inconsistencies in record-keeping, and delays in reporting. This study aims to design and develop a web-based school inventory information system using the Waterfall method to support integrated inventory recording, tracking, and reporting. The Waterfall method is implemented through sequential stages, including requirements analysis, system design, implementation, testing, and deployment. System testing is conducted using functional testing (black box testing) and user trials. The results indicate that all system functions operate as expected, modules are well integrated, and the system is capable of generating accurate inventory reports based on specified periods. Overall, the developed system has been proven to enhance the effectiveness, efficiency, and accuracy of school inventory management, while also supporting decision-making related to the procurement and maintenance of educational facilities and infrastructure.